BODY IMAGE DIFFERENCES IN BODY IMAGE BETWEEN BEFORE AND AFTER MASTECTOMY TO BREAST CANCER CLIENTS AT RSUD DR. SAIFUL ANWAR MALANG - Slamet Indriyanto (Jurnal Ilmiah Kesehatan Media Husada, 2022)
ABSTRACT Indriyanto, Slamet. 2021. Differences in Body Image Between Before And After Mastectomy To Breast Cancer Clients At RSUD Dr. Saiful Anwar Malang. Thesis. Bachelor of Nursing, Maharani Health College Malang. Supervisors: (1) Ns. Wiwik Agustina, S.Kep., M. Biomed, (2) Ns. Rahmawati Maulidia, M.Kep. Breast cancer is one of the most common types of cancer in Indonesia and mastectomy is a rational and effective treatment procedure to prevent the spread and disposal of cancer cells. Body image undergoes many changes during breast cancer therapy and treatment, the impact of these changes affects client perception, sexuality, and social function. The purpose of this study is to identify body image before and after the mastectomy, and whether there is a change in body image between before and after the mastectomy. The study used the BREAST-Q Version 2.0 Mastectomy Module and Pre-Post Operative Scales questionnaire. The design of this study is comparative study with cross sectional analysis. The results of the study, obtained body image before mastectomy almost all respondents (90%) with negative body image. While body image after mastectomy, obtained by all respondents (100%) have a negative body image. Wilcoxon signed rank test results showed a difference in body image between before and after the mastectomy, with a value of p: 0.005 smaller than α= 0.05 Body image has changed before the mastectomy, even decreasing after the mastectomy. Keywords: Breast Cancer, Body image, Mastectomy.